Movies under the influence - Szczepaniak-Gillece, Jocelyn (Book collections on Project MUSE., 2024)
"Exploring the effects of intoxicants on film spectatorship, Movies under the Influence charts their entangled histories from early cinema through the psychedelic 1970s. Jocelyn Szczepaniak-Gillece examines the implicit relationship mind-altering substances suggest between mass media, spectatorship, and governmental regulation, offering a new angle from which to understand cinema's lasting role in evolving American culture"--